Theoretical framework of the causes of construction time and cost overruns - Ullah, Kaleem; Abdullah, Abd Hadi; Nagapan, Sasitharan; Suhoo, S; Khan, M S (IOP Publishing, 2017)
Any construction practitioner fundamental goal is to complete the projects within estimated duration and budgets, and expected quality targets. However, time and cost overruns are regular and universal phenomenon in construction projects and the construction projects in Malaysia has no exemption from the problems of time overrun and cost overrun. In order to accomplish the successful completion of construction projects on specified time and within planned cost, there are various factors that should be given serious attention so that issues such as time and cost overrun can be addressed. This paper aims to construct a framework for the causes of time overrun and cost overrun in construction projects of Malaysia. Based on the relevant literature review, causative factors of time overrun and cost overrun in Malaysian construction projects are summarized and the theoretical frameworks of the causes of construction time overrun and cost overrun is constructed. The developed frameworks for construction time and cost overruns based on the existing literature will assist the construction practitioners to plan the efficient approaches for achieving successful completion of the projects.